Spain : Demonstration at Royal Albert Hall (circular) - Middleton, J. S.
011-0012-001 Telegraphic Address: " LABREPCOM. SOWEST. LONDON.' Telephones: VICTORIA 8016, 8017, 8018, 8019 THE LABOUR PARTY TRANSPORT HOUSE (South Block), SMITH SQUARE, LONDON. S.W.1 Secretary ; J. S. MIDDLETON 1st December 1937. LONDON TRADES COUNCIL. 24, THAVIES INN, HOLBORN. E.C.1. Dear Sir or Madam, SPAIN: DEMONSTRATION AT ROYAL ALBERT HALL SUNDAY, DECEMBER 19, 1937. The Spain Campaign Committee of the National Executive is to hold a great Mass Demonstration in the Royal Albert Hall on the evening of Sunday, December 19, 1937, as part of a series of similar meetings to be held throughout the country. The speakers at the albert Hall will be:- Rt. Hon. C.R. Attlee, M.P. Rt. Hon. Herbert Morrison, M.P. Rt. Hon. A.V. Alexander, M.P. Hon. Sir Stafford Cripps, K.C., M.P. Mrs. Barbara Ayrton Gould, J.P. Miss Ellen Wilkinson, M.P. Mr. James Walker, M.P. The Chair will be taken by Mr. George Dallas, J.P. at 7 p.m. Selections will be rendered by the London Labour Choral Union. Organise Immediate Collections The Spain Campaign Committee of the National Executive earnestly hope for a really substantial collection at this Albert Hall meeting, the proceeds of which will go to the relief of Spanish distress. A special appeal will be made at the Hall for generous contributions and the Campaign Committee suggest that it would be practicable for local Labour Parties and other affiliated organisations to organise now in their own areas a special collection, the results of which can be handed up to the platform on December 19 and announced as being from the particular organisation concerned. Admission will be by ticket Tickets are available for this Demonstration at the prices of 6d and 1/-, and are obtainable from the above address or the London Labour Party Office, 258-262, Westminster Bridge Road, London, S.E. 1. The need of our Spanish comrades is an urgent one and we depend upon the London Labour Movement to pack the Royal Albert Hall on December 19th, and to demonstrate its support of our heroic Spanish comrades. Yours sincerely, J.S.Middleton Secretary. To all Trade Union District Committees, and Branches in Extra-London. 292/946/11/12